O valor do mito em Acauã de Inglês de Sousa - FREITAS, Antonio Marcos Lopes (2019)
The present research titled - The value of the myth in Acauã de Inglés de Sousa - had as objective to reflect on the meaning of the myth and its influence in the formation of the cultural identity of the amazonian people. For that, it was necessary to unravel the meaning of the myth and what its influence in the societies in which it forms part as a cultural expression. In this process we realize that myth is an extremely complex term, because in order to define it, we have to take into account several contexts. Therefore, the research studied the myth from different perspectives: literary, historical, anthropological. In all the studied perspectives we perceive that the myth is considered a narrative that contributes in the explanation of the origin of a phenomenon or human experience that influences in the cultural conduct of the man. Another proposal of the work was to relate the myth to the cultural formation of a people. This proposal had the purpose of discovering the influence that the myth exerts on the cultural formation of the individual. Through the theories studied on the subject, we came to the conclusion that myth and culture can be considered as the basis of the development of human practices and actions responsible for the construction of reality and the world. For a better understanding, we reserve a moment of research to conceptualize culture and cultural identity, because we understand that, in order to establish a relationship between cultural formation and myth, it is necessary to define what both terms mean. After the presentations of theories about myth, culture and cultural identity, this work made an analysis of the "Acauã" short story of Sousa 1893, where he showed some references of Amazon legends present in the story. The methodology used was based on studies of Campbell (1991), Cassirer (1992), Chauí (2000), Eliade (1978), Rocha (1996), Vernant (1992), among others. myth in their works.